Validation of a paper‐disk approach to facilitate the sensory evaluation of bitterness in dairy protein hydrolysates from a newly developed food‐grade fractionation system. Issue 3 (16th June 2017) - Murray, Niamh M.; O'Riordan, Dolores; Jacquier, Jean‐Christophe; O'Sullivan, Michael; Cohen, Joshua L.; Heymann, Hildegarde; Barile, Daniela; Dallas, David C.
Abstract: Casein‐hydrolysates (NaCaH) are desirable functional ingredients, but their bitterness impedes usage in foods. This study sought to validate a paper‐disk approach to help evaluate bitterness in NaCaHs and to develop a food‐grade approach to separate a NaCaH into distinct fractions, which could be evaluated by a sensory panel. Membrane filtration generated < 0.2‐µm and <3‐kDa permeates. Further fractionation of the <3‐kDa permeate by flash‐chromatography generated four fractions using ethanol (EtOH) concentrations of 5, 10, 30, and 50%. As some fractions were poorly soluble in water, the fractions were resolubilized in EtOH and impregnated into paper disks for sensory evaluation. Bitterness differences observed in the membrane fractions using this sensory evaluation approach reflected those observed for the same fractions presented as a liquid. The flash‐chromatography fractions increased in bitterness with an increase in hydrophobicity, except for the 50% EtOH fraction which had little bitterness. Amino acid analysis of the fractions showed enrichment of different essential amino acids in both the bitter and less bitter fractions. Practical applications: The developed food‐grade fractionation system, allowed for a simple and reasonably scaled approach to separating a NaCaH, into physicochemically different fractions that could be evaluated by a sensory panel. The method of sensory evaluation used in this study, in which NaCaH samples are impregnated into paper disks, provided potential solutions for issues such as sample insolubility and limited quantities of sample. As the impregnated paper‐disk samples were dehydrated, their long storage life could also be suitable for sensory evaluations distributed by mail for large consumer studies. The research, in this study, allowed for a greater understanding of the physicochemical basis for bitterness in this NaCaH. As some essential amino acids were enriched in the less bitter fractions, selective removal of bitter fractions could allow for the incorporation of the less bitter NaCaH fractions into food products for added nutritional value, without negatively impacting sensory properties. There is potential for this approach to be applied to other food ingredients with undesirable tastes, such as polyphenols.